Association of cytokine gene polymorphisms with psoriasis in cases from the Nile Delta of Egypt - Ahmad A Settin; Hanaa A Hassan; Rizk A El-Baz; Tahia A Hassan (Wolters Kluwer Medknow Publications, 2011)
Background: Psoriasis is a chronic inflammatory skin disease with an immunogenetic background. This work was planned to check for the association of polymorphisms related to cytokine genes TNF-α-308 (G/A), IL-10 -1082 (G/A), IL-6 -174 (G/C), and IL-1Ra (VNTR) with psoriasis in cases from Egypt. Materials and Methods: This work included 46 cases with psoriasis recruited from the Dermatology Departments, University Hospitals, Nile Delta region of Egypt. They included 14 males and 32 females with an age mean ± SD of 46.68 ± 12.16 years and range of 15-70 years. Their genotypes were compared to 98 healthy controls of matched age and sex from the same locality. Genotyping was done through deoxyribonucleic acid amplification using PCR with sequence specific primers for polymorphic alleles. Results: Compared to controls, cases showed significant higher frequency of certain genotypes including IL-6 -174 CC (P < 0.001, OR = 6.7), IL-10 -1082 GG ( P < 0.05, OR = 5.1), and TNF-α-308 GG ( P < 0.05, OR = 3.7). TNF-α-308 GG and IL-10 -1082 GG genotypes were higher among cases with plaque subtype of moderate severity. Combined heterozygosity for IL-10 GA, IL-6 GC with TNF GA showed a significant low frequency among studied cases. Conclusion: Genetic polymorphisms related to IL6, IL10, and TNF-α genes showed a particular pattern of association with psoriasis that may have a potential impact on disease counseling and management.